2014
DOI: 10.1589/jpts.26.517
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stair Walking Training on the Balance Ability of Chronic Stroke Patients

Abstract: [Purpose] The purpose of this study was to evaluate the effects of stair walking training on balance ability of chronic stroke patients. [Subjects and Methods] Forty stroke patients were allocated equally and randomly to an experimental group and a control group. The experimental group undertook 30 minutes of training therapy and 30 minutes of walking exercise on stairs with flat surfaces. The control group undertook 30 minutes went of training therapy and 30 minutes of walking exercise on a flat surface. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Most of the research on quiet standing makes use of a kinetic measurement method in which the anterior-posterior and medial-lateral displacements of the COP are calculated on a force platform 11 ) . In general, evaluation of balance ability of stroke patients depends on the following four indices: mean COP velocity (velocity), area of the 95% confidence ellipse (area), average anterior-posterior displacement (Ymean), and average medial-lateral displacement (Xmean) 12 , 13 , 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on quiet standing makes use of a kinetic measurement method in which the anterior-posterior and medial-lateral displacements of the COP are calculated on a force platform 11 ) . In general, evaluation of balance ability of stroke patients depends on the following four indices: mean COP velocity (velocity), area of the 95% confidence ellipse (area), average anterior-posterior displacement (Ymean), and average medial-lateral displacement (Xmean) 12 , 13 , 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The current study demonstrated that wearable robot-assisted training could even be implemented in simple stair environment as a feasible rehabilitation approach. Previous studies showed that mild stair training in chronic stroke could improve physical activity level [11], trunk stability and balance [10,12], walking speed and endurance [10,35]. The robot-assisted stair training described in the current study required only one skilled trainer walking alongside the stroke subjects for safety and verbal cueing, while the posture adjustment for foot drop correction could be handled automatically by the robot itself [32].…”
Section: Discussionmentioning
confidence: 97%
“…These gait training systems con ned the users in constant treadmill-like setting, but the real-world walking environment would involve varying terrains, like obstacles, slopes, and stairs. Some studies showed intensive stepping training on stairs and over-ground could improve walking speed and balance in sub-acute [10] and chronic stroke [11,12]. Early stroke rehabilitation on stair negotiation could potentially enhance gait reeducation for better outcome on gait independency at hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…This study measured the static pressure of the subject's feet to examine the weight distribution of the feet in a standing posture. 15) The evaluation of this study measured the foot pressure in a ten-second stand-up before and after intervention and measured the average value three times.…”
Section: )mentioning
confidence: 99%